Design of a Switched Reluctance Motor Controller Applied to Electric Vehicles Traction. - Carlos Eduardo dos Santos Almeida (2019)
Switched reluctance motors (SRM) are a suitable and cheaper alternative for current electric vehicle (EV) powertrain topologies due to low weight, high torque/size ratio and simple construction, without permanent magnets and a minimum amount of copper. The main setback that these motors encounter is the high torque ripple, mainly due to the highly nonlinear torque generation mechanism. Torque ripple leads to mechanical vibrations that require unnecessary wear in the mechanical powertrain. In conventional torque sharing function (TSF) control, the torque produced by the machine cannot follow the expected torque for an extended speed range, mostly due to the imposed demagnetization of the outgoing phase at high speeds, resulting in poor performance and causing a high torque ripple. The main goal of this work is to design and validate a new SRM control method suitable for EV propulsion. The proposed controller applies a feedback loop that improves the weakness of the conventional methods, keeping a fast dynamic response. The simulation results show that torque ripple can effectively be reduced for a high torque and speed range. The researched algorithm is developed using Matlab/Simulink, basing the validation on experiments with a 60kW SRM, 12/8 poles prototype designed using finite element methods (FEM).